Circulation of canine viruses in free-ranging Italian wolves (Canis lupus italicus) from three Italian regions - Musto, Carmela <1981> (Alma Mater Studiorum - Università di Bologna, 2021)
In this study, the duodenum, spleen, tongue, and lungs were sampled from 56 Italian wolves who died between 2017 and 2020. The aim of the study was to evaluate the presence and spread of DNA and RNA viruses in the wolf population examined, relating the virological results to: year of sampling, region of origin, sex, age, season, genetic determination of the species, nutritional conditions, causes of death, matrices examined. In addition, the presence or absence of co-infections was evaluated. Through molecular methods, the presence of genomic DNA of three important DNA viruses was investigated, i.e.: Canine Parvovirus type 2 (CPV-2), Canine Adenovirus type 1 (CAdV-1), Canine Adenovirus type 2 (CAdV-2). Furthermore, the presence of genomic RNA of the important RNA viruses, Canine Enteric Coronavirus (CCoV) and Canine Distemper Virus (CDV), was also investigated. The results showed that the virus with the highest prevalence in the wolf population studied was CPV-2, found in 78.6% of subjects (44/56). The prevalence of CAdV was 17.9% (10/56), in particular CAdV-1 (12.5% - 7/56) and CAdV-2 (5.4% - 3/56). The results of the molecular investigations in RT-PCR of the two RNA viruses (CCoV and CDV) did not give positive results in the study population. In this study it was observed that the majority of wolves that resulted positive were in good nutritional conditions, thus excluding a direct cause of death from CPV-2, CAdV-1, and CAdV- 2 infections. Moreover, the prevalence obtained in this study suggests that, during the years here studied, the circulation of CAdV-1 and CAdV-2 in Italian wolves of the three sampled regions was sporadic, proving consistent with sporadic and short-lived introductions of the virus in these populations. However, the situation for CPV-2 is different as there was a circulation that suggests a pattern of continuous and lasting endemic exposure over time.